Economics of Multifunctional Forestry in the Sámi People Homeland Region - Vesa-Pekka Parkatti; Olli Tahvonen (Fondazione Eni Enrico Mattei (FEEM), 2020)
We study forestry in the Sámi people homeland region to understand an ongoing conflict between conventional forest logging and maintaining forests as reindeer pastures for indigenous people. We use a detailed model that simultaneously includes timber production, carbon storage in living biomass, deadwood and wood products, negative effects on reindeer husbandry, and a flexible optimization between rotation forestry (cf. clearcuts) and forestry that maintains continuous forestcover. We show that the profitability of conventional forestry is based on utilizing existing forest stands, an outcome that can be understood as forest capital mining. By varying the carbon price between exteuro0 tCO2 and exteuro40 tCO2, we show that the optimal solutions based on a 3% interest rate are always continuous cover forestry. A carbon price of exteuro60 - exteuro100tCO2 implies that it is optimal to give up timber production and utilize forests for carbon storage and reindeer pasture only. Given the present forest management practices and an old-growth forest as the initial state, the carbon choke price decreases to exteuro14– exteuro20 CO2. The optimal choice between timber production and utilizing forests purely for carbon storage and reindeer husbandry may depend on the initial forest state. The choice between maintaining old-growth forest and converting land to timber production, as determined by dynamic economic analysis, is incompatible with the frequently applied approach based on carbon debt and the carbon payback period.
Keywords: Q2; Q23; Q24; Q28; 330; Arctic Forestry; Indigenous Peoples; Sámi; Continuous Cover Forestry; Uneven-Aged Forestry; Carbon Sequestration; Reindeer Husbandry; Carbon Debt; Payback Period